The role of specialized pro-resolving mediators in the control of inflammation in periodontal disease: A literature review (2024)
Introduction: The main etiological factors in periodontitis are the host inflammatory response and a dysbiosis in the interaction with the oral microbiome. Therefore, the primary goal of periodontal therapy is the elimination of dental biofilm, promoting the regulation of the host defense mechanisms underlying chronic inflammation. Specialized pro-resolving mediators (SPMs) are endogenous signaling molecules released during inflammation to control the adverse effects of an exacerbated inflammatory response and promote its resolution. This process is a coordinated response aimed at restoring tissue integrity and function, ultimately returning the system to homeostasis. The discovery of new families of lipid mediators derived from omega -6 fatty acids, such as lipoxins, and chemical mediators derived from omega-3 fatty acid such as, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and n-3 docosapentaenoic acid (DPA), has provided promising pathways as a potential adjunctive treatment to mechanical therapy. Objective: This literature review seeks to integrate concepts of the role of pro-resolving lipid mediators in the inflammatory process of periodontal disease. Literature search strategy and study selection: An electronic search was conducted in the MEDLINE/PUBMED database to select articles that evaluated the role of pro-resolving mediators, focusing on resolvins, in controlling inflammation in periodontal disease from 2010 to 2024. A total of 51 articles were included. Results: There is strong evidence that ω-3 PUFAs are useful for controlling inflammation across different types of diseases. However, it remains unclear how dietary supplementation with ω-3 PUFAs affects periodontal parameters and periodontal treatment outcomes. Since pro-resolving mediators are still a relatively new immunomodulatory therapy in relation to periodontitis, there is no consensus on the timing and concentration of supplementation with ω-3 PUFAs. Resolution of inflammation mediated by RvE1 reduces neutrophil infiltration, induces neutrophil apoptosis, and attracts non-phlogistic macrophages that phagocytose apoptotic neutrophils and microorganisms, thereby clearing chronic inflammatory lesions through efferocytosis. Resolvins enhance the resolution of inflammation in an anticipatory manner, driven by receptor agonists, instead of inhibiting processes, as is the case with non-steroidal anti-inflammatory drugs (NSAIDs), which suppress COX or antagonize receptors. The reduced activity of osteoclasts after RvE1 treatment appears to significantly regulate alveolar bone loss in animal models. RvE1 reduces osteoclast differentiation in vitro and enhances osteoblast production in vivo. Conclusion: Treatment of experimental periodontitis with lipid mediators resulted in complete resolution of inflammation and significant regeneration of soft and hard tissues, promoting the restoration of homeostasis however, there is still limited evidence in humans.